Performance measurement in the service business: the facilities management function - Sapri, Maimunah; Kaka, Amar; Alias, Buang (2005)
The nature of performance measurement has changed over the past few decades. Generally performance measurement indicates successful management in the fulfilment of organisation goals. In service businesses measuring customer satisfaction and service quality has become an industry standard and as FM is becomes more widely recognised as a component in the business value chain and corporate strategic objectives, the adoption of performance indicators that relate directly to the core business driver is key to success. This paper examines the state of knowledge of performance measurement in a facilities management context, expounds and reveals the role that performance measurement plays in the overall efficiency of the FM service function in relation to service business operation. The paper suggests that a fully developed performance measurement solution can deliver as a business tool whilst acting as a driver in the innovation process of service organisation.